2006
DOI: 10.2320/matertrans.47.532
|View full text |Cite
|
Sign up to set email alerts
|

A TiNiCu Thin Film Micropump Made by Magnetron Co-Sputtered Method

Abstract: Thin film SMAs have the potential to became a primary actuating mechanism for micropumps. In this study, a micropump driven by TiNiCu shape memory thin film is designed and fabricated. The micropump is composed of a TiNiCu/Si bimorph driving membrane, a pump chamber and two inlet and outlet check valves. The property of TiNiCu films and driving capacity of TiNiCu/Si bimorph driving membrane are investigated. The film surface shows a smooth and featureless morphology without any cracks, and the hysteresis width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…They reported that TiNi binary SMAs exhibited fewer morphological changes and a lower reduction of dehydrogenase activity of epithelia cell cultures than did TiNiCu ternary SMAs, indicating that the release of the Cu ions may lead to a higher cytotoxicity of TiNiCu SMAs. Zhang et al [20] reported a TiNiCu thin-film micropump made by magnetron co-sputtered method. According to their study, the TiNiCu thin-film micropump exhibited a high pumping yield, high working frequency, stable driving capacity, and long fatigue lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that TiNi binary SMAs exhibited fewer morphological changes and a lower reduction of dehydrogenase activity of epithelia cell cultures than did TiNiCu ternary SMAs, indicating that the release of the Cu ions may lead to a higher cytotoxicity of TiNiCu SMAs. Zhang et al [20] reported a TiNiCu thin-film micropump made by magnetron co-sputtered method. According to their study, the TiNiCu thin-film micropump exhibited a high pumping yield, high working frequency, stable driving capacity, and long fatigue lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Their martensitic transformation temperatures (M s ) are close to room temperature. Moreover, the addition of Cu is very important for applications in robotic devices or actuators 5,6 because it inhibits the formation of R-phase which is an undesirable phase that causes a nonlinear correlation between the strain (ε) and the change in electrical resistivity (Δr/r 0 ). When 5 % at.…”
Section: Introductionmentioning
confidence: 99%
“…When 5 % at. of Cu is added, a linear correlation is achieved, which allows very good control of the position of the actuator [2][3][4][5][6][7][8] . The correlation study of the microstructural evolution during the recovery process after an "amorphization" with mechanical, electrical and thermal properties is important for the applications of Ti-Ni-Cu system, because by controlling the microstructure with the thermomechanical treatment, the mechanical or electrical response of the alloy can be predicted, for example the position of an actuator.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to produce these films. Magnetron sputtering is the most suitable method due to lower contamination and high purity films and adjustment of the atomic ratio, growing structure and film thicknesses by controlling the deposition parameters [5][6][7][8][9]. The basis of the shape memory is the transformation of phases [10].…”
Section: Introductionmentioning
confidence: 99%